Juror gender and confession evidence: an exploratory study of effects on empathy and trial outcomes for juvenile defendants - Najdowski, Cynthia J. (Journal of experimental criminology, 2020)
Objectives We explored how relations among juror gender, confession evidence, and empathy impacted verdicts for a juvenile defendant accused of a serious crime. Methods Jury-eligible women and men (N = 132) participated in a mock trial involving a girl defendant who had either maintained her innocence, confessed voluntarily, or confessed under coercion. Participants reviewed case materials, received juror instructions, and reported their verdict and empathy for the girl defendant. A manipulation check ensured participants attended to details surrounding the confession and participants were grouped by whether they perceived the confession as voluntary or coerced. A logistic regression analysis examined main and interactive effects of juror gender and perceived-confession condition on jurors’ verdicts, and the PROCESS regression macro-examined whether effects revealed therein could be explained by empathy toward the juvenile. Results Juror gender did not have a significant indirect effect on verdicts in either the no-confession, B = .05, 95% CI [− .005, .85], or perceived-coerced-confession conditions, B = − .12, 95% CI [− .36, .02]. However, women’s lower levels of empathy translated into a higher conviction rate among women versus men for the juvenile who was perceived as confessing voluntarily, B = − .28, 95% CI [− .75, − .02]. Conclusions Women and men differ in ways that may sometimes produce outcomes that are less favorable to juvenile defendants. Implications for jury practice and process are considered.